Outcomes of the Victorian Safewards trial in 13 wards: Impact on seclusion rates and fidelity measurement. (27th September 2017) - Fletcher, Justine; Spittal, Mathew; Brophy, Lisa; Tibble, Holly; Kinner, Stuart; Elsom, Steve; Hamilton, Bridget
Abstract: Restrictive practices are used in response to conflict and aggression in psychiatric inpatient settings. Reducing such practices is the focus internationally of policy and legislative change, many initiatives, and a growing body of research. Safewards is a model and a set of 10 interventions designed to reduce conflict and containment in inpatient services. In the current study, we aimed to assess the impact of implementing Safewards on seclusion in Victorian inpatient mental health services in Australia. The study used a before‐and‐after design, with a comparison group matched for service type. Thirteen wards opted into a 12‐week trial to implement Safewards and 1‐year follow up. The comparison group was all other wards ( n  = 31) with seclusion facilities in the jurisdiction, matched to service type. Mandatorily‐reported seclusion event data for all 44 wards over a 15‐month period were analysed using negative binomial regression. Adherence to Safewards was measured via fidelity checklists at four time points: twice during the trial, post‐trial, and at 1‐year follow up. Seclusion rates were reduced by 36% in Safewards trial wards by the 12‐month follow‐up period (incidence rate ratios (IRR) = 0.64, ) but in the comparison wards seclusion rates did not differ from baseline to post‐trial (IRR = 1.17) or to follow‐up period (IRR = 1.35). Fidelity analysis revealed a trajectory of increased use of Safewards interventions after the trial phase to follow up. The findings suggest that Safewards is appropriate for practice change in Victorian inpatient mental health services more broadly than adult acute wards, and is effective in reducing the use of seclusion.